Impact of Disinvestment on Indian Public Sector Enterprises: A Case Study of Minerals and Metals Units - Narta, S. S.; Verma, Om Prakash; Singh, Gagan (Indian Journal of Finance, 2010)
Public enterprises conceived as an instrument for maximizing the welfare function have a major influence in the development of a mixed economy like India. They are referred to as 'Commanding Heights Of The Indian Economy'. In 1947, when the country became independent, there were various socio-economic problems confronting the country, which needed to be dealt with in a planned and systematic manner. India at the time was an agrarian economy with a weak industrial base, low level of savings, inadequate investment and lack of infrastructural facilities. There existed considerable inequalities in income and levels of employment, glaring regional imbalances in economic development and lack of trained manpower. As such, the State's intervention in all the sectors of the economy was inevitable since the private sector neither had the necessary resources, the managerial and scientific skill, nor the will to undertake risks associated with large long-gestation investments. Given the type and range of problems faced by the country on the economic, social and strategic fronts, it become a pragmatic compulsion to use the public sector as an instrument for self-reliant economic growth.